2022
DOI: 10.1186/s40824-022-00255-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermodynamic, pharmacokinetic and theranostic properties of polymeric micelles via hydrophobic core-clustering of superparamagnetic iron oxide nanoparticles

Abstract: Background Superparamagnetic iron oxide nanoparticles (SPIO) have been applied for decades to design theranostic polymeric micelles for targeted cancer therapy and diagnostic MR imaging. However, the effects of SPIO on the physicochemical, and biological properties of polymeric micelles have not yet been fully elucidated. Therefore, we investigated potential effect of SPIO on the physical and biological properties of theranostic polymeric micelles using representative cancer drug (doxorubicin; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Micelle size is influenced both by the size [ 21 , 49 , 83 , 84 ] and the clustering [ 86 ] of loaded SPIONs. For a given SPION-loaded amount, increasing SPIONs size leads to an enlargement of MPMs.…”
Section: Fabrication Of Magnetic Polymeric Micellesmentioning
confidence: 99%
See 3 more Smart Citations
“…Micelle size is influenced both by the size [ 21 , 49 , 83 , 84 ] and the clustering [ 86 ] of loaded SPIONs. For a given SPION-loaded amount, increasing SPIONs size leads to an enlargement of MPMs.…”
Section: Fabrication Of Magnetic Polymeric Micellesmentioning
confidence: 99%
“…For a given SPION-loaded amount, increasing SPIONs size leads to an enlargement of MPMs. The amount of loaded SPIONs also influences the micelle diameter, as elegantly investigated by Jiang et al [ 86 ]. In this work, the SPION-free micelles presented a diameter of 24 ± 3 nm, and the diameters increased to 80 ± 13, 100 ± 9 and 108 ± 8 nm, respectively, when SPIONs were loaded into the micelles by weight ratio of 15, 30, and 50% [ 86 ].…”
Section: Fabrication Of Magnetic Polymeric Micellesmentioning
confidence: 99%
See 2 more Smart Citations
“…To enhance the quality of MRI, researchers have proposed the use of amphiphilic polymers to encapsulate hydrophobic SPIO nanocrystals and facilitate their dispersion in aqueous solutions through micelle formation [ 2 , 11 , 12 ]. Moreover, several studies have shown that these strategies have significant potential for improving the sensitivity of MRI [ 13 , 14 , 15 ]. A significant enhancement in T 2 relaxivity (r 2 ) can be achieved using synergistic magnetism through the encapsulation of multiple SPIO nanocrystals in the hydrophobic core of micelles to form magnetic nanoclusters [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%